2019
DOI: 10.1186/s13104-019-4704-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequence of a pathogenic Corynebacterium ulcerans strain isolated from a wild boar with necrotizing lymphadenitis

Abstract: ObjectivesCorynebacterium ulcerans can colonize a wide variety of animals and also humans are infected, typically by zoonotic transmission. Symptoms range from skin ulcers or systemic infections to diphtheria-like illness. In contrast, Corynebacterium pseudotuberculosis is widely distributed among herds of sheep, goats and other farm animals, where it causes high economic losses due to caseous lymphadenitis. Here we describe the genome sequence of an atypical C. ulcerans strain isolated from a wild boar with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
(11 reference statements)
0
9
0
1
Order By: Relevance
“…We have recently isolated an atypical C. ulcerans strain, W25, associated with necrotizing lymphadenitis in a wild boar and published the genome sequence (Busch et al 2019). While the size of the genome is consistent with other C. ulcerans genomes, G ?…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…We have recently isolated an atypical C. ulcerans strain, W25, associated with necrotizing lymphadenitis in a wild boar and published the genome sequence (Busch et al 2019). While the size of the genome is consistent with other C. ulcerans genomes, G ?…”
Section: Introductionmentioning
confidence: 69%
“…While the size of the genome is consistent with other C. ulcerans genomes, G ? C content of the W25 was approximately 1.0% higher than other C. ulcerans strains (Busch et al 2019). It may reflect significant variations in the gene content and virulence properties of this strain than other C. ulcerans isolates.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Nevertheless, given that we can perceive a slight gray colour in the GENPPI heat map, we believe that this species has some protein similarity to C. pseudotuberculosis . In this case, the literature describes the species C. pseudotuberculosis , C. diphtheriae , and C. ulcerans as being evolutionarily related (Busch et al , 2019) (McNamara, Cuevas, and Songer 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Recently the genome sequence of the atypical C. ulcerans strain W25, isolated from a wild boar with necrotizing lymphadenitis, was published [ 21 ]. Taxonomic analyses of the genome sequence data revealed that this isolate is clustered with two different isolates previously annotated as C. ulcerans KL1196 (identical to CVUAS6455 [ 17 ]) and C. pseudotuberculosis PO100/5 [ 22 ] and clearly delineated from other published C. ulcerans strains [ 23 ].…”
Section: Introductionmentioning
confidence: 99%